Intelligent Computing and Optimization for Sustainable Development - Veena Grover; Rajesh Kumar Dhanaraj; Balamurugan Balusamy; Gopal Rathinam (Chapman and Hall/CRC, 2025)
This book presents insights into how Intelligent Computing and Optimization techniques can be used to attain the goals of Sustainable Development. It provides a comprehensive overview of the latest breakthroughs and recent developments in sustainable, intelligent computing technologies, applications, and optimization techniques across various industries, including business process management, manufacturing, financial sector, agriculture, financial sector, supply chain management, and healthcare. It focuses on computational intelligent techniques and optimization techniques to provide sustainable solutions to many problems.Features: Provides insights into the theory, implementation, and application of computational intelligence techniques in many industries Includes industry practitioner perspectives and case studies for a better understanding of sustainable solutions Highlights the role of intelligent computing and optimization as key technologies in decision-making processes and in providing cutting-edge solutions to real-world problems Addresses the challenges and limitations of computational approaches in sustainability, such as data availability, model uncertainty, and computational complexity, while also discusses emerging opportunities and future directions in the field This book will be useful for professionals and scholars looking for up-to-date research on cutting-edge perspectives in the field of computational intelligent and optimization techniques in the areas of agriculture, industry, financial sector, business automation, renewable energy, optimization, and smart cities.The Open Access version of this book, available at http://www.taylorfrancis.com, hasbeen made available under a Creative Commons [Attribution-Non Commercial-NoDerivatives (CC BY-NC-ND)] 4.0 license.